ANALISIS CLUSTER UNMET NEED KELUARGA BERENCANA DI INDONESIA - Sih Kawuri Sejati (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Control of population through Family Planning and Family Development is one of the strategic issues listed in the 2015-2019 RPJMN. One of the problems faced in family planning services is the high number of unmet need in Indonesia. Apart from the high national unmet need, there is still a high gap for unmet need in the provinces in Indonesia. The unmet need gap between provinces in Indonesia has caused there is no solution that can solve this problem. This study aims to group provinces in Indonesia based on the level of unmet need and the factors that influence it. Using secondary data from BPS and cluster analysis, the result of four provincial groups were obtained. Nearby provinces tend to cluster in the same cluster.